Enantioseparation and dissipation monitoring of oxathiapiprolin in grape using supercritical fluid chromatography tandem mass spectrometry. Issue 21 (21st September 2020) - Liu, Qianyu; Dong, Fengshou; Xu, Jun; Liu, Xingang; Wu, Xiaohu; Li, Runan; Jiang, Duoduo; Wu, Xiuming; Liu, Yingchao; Zheng, Yongquan
Abstract: Oxathiapiprolin is a chiral fungicide used in China for the prevention and treatment of grape downy mildew, but its potential risk could be inaccurately assessed without distinguishing its enantiomers. In this study, an effective and sensitive chiral analytical method was first established for quantification of oxathiapiprolin enantiomers using supercritical fluid chromatography tandem mass spectrometry. Baseline separation for oxathiapiprolin enantiomers was achieved for less than 3 min by using a Lux Cellulose‐2 chiral column with the resolution of 1.51. The elution order of the eluting enantiomers was identified as (−)‐oxathiapiprolin and (+)‐oxathiapiprolin by an optical rotation detector. The grape samples were extracted by QuEChERS method, with the average recoveries of each enantiomer in grapes were in the range of 88.1–111.8% and the relative standard deviations were less than 18.9%. The enantioselective analysis of the dissipation of oxathiapiprolin in field grape samples showed that (−)‐oxathiapiprolin was dissipated faster than (+)‐oxathiapiprolin. The results indicate that this proposed method could provide data support for the risk assessment of oxathiapiprolin in agricultural produces in a more accurate way.